DOUBLE CONSCIOUSNESS IN FRIDA KAHLO’S “SELF PORTRAIT WITH CROPPED HAIR” - Satheesh, Vaishnavi; Narayanan, Anjana; Aich, Shibani Chakraverty (International Journal of Psychosocial Rehabilitation, 2020)
Frida Kahlo was a Mexican artist, who was considered a remarkable impression in the panorama of aestheticism. She used art as a great weapon to express her physical and mental challenges. The role of an activist admired her as an icon of female creativity in the Feminist movement. “Self Portrait with Cropped Hair” was considered to be revolutionary work, as the portrait posits to break the conventions that prevailed in her age. The paper analyses how the concept of doubleconsciousness gave birth to an astonishing art enriched with meanings beyond expression. It also explores the contributions given by the mental conspiracies resided in Frida Kahlo the production of such outlandish creation of art. The patronizing mentality of the society towards the female representatives is being questioned through her art. This article also scrutinizes whether the male overshadowing is required for the freedom of female expressions.